(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This research is intended to analyze the influence of motivation, discipline, work environtment and work commitment on the employee performance of UD. Sregep Yogyakarta. The respondents consist of 70 respondents. Questionnaire are used to collect data from the respondents and the data were analized by Multiple Regression Analysis. The result of the studyindicates that: (i). Motivation has no significant influence on the employee performance (ii). Discipline has significant influence on the employee performance (iii). Work environtment has no significant influence on the employee performance (iv) Work commitment has significant influence on the employee performance (v) Motivation, discipline, work environment, and work commitment simultaneously has significant influence on the employee performance.